2020
DOI: 10.2147/dddt.s243420
|View full text |Cite
|
Sign up to set email alerts
|

<p>Isoliquiritigenin Attenuates UUO-Induced Renal Inflammation and Fibrosis by Inhibiting Mincle/Syk/NF-Kappa B Signaling Pathway</p>

Abstract: Chronic kidney disease (CKD) is a global nephrotic syndrome characterized by chronic inflammation, oxidative stress and fibrosis in the kidney. Isoliquiritigenin (ISL), a flavonoid from licorice, has historically been reported to inhibit innate immune responses to inflammation and fibrosis in vivo. However, the effect of ISL on CKD progression is largely unknown. Materials and Methods: In this study, we employed the inflammatory and fibrotic models of LPS/TGF-β-induced bone marrow-derived macrophages (BMDM) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(51 citation statements)
references
References 37 publications
0
51
0
Order By: Relevance
“…Similarly, 2-hydroxy-3’,5,5’-trimethoxychalcone (DK-139) ( 58 , Figure 13 ) inhibited the Toll-like receptor 4-mediated inflammatory response through suppression of the Akt//IKK/NF-κB signaling pathway in BV2 microglial cells [ 148 ]. In addition, isoliquiritigenin [ 149 , 150 , 151 ], flavokawain A and B [ 152 ], licochalcone A [ 153 ], cardamonin [ 154 , 155 , 156 ] and xanthohumol [ 157 ] all showed anti-inflammatory and anticancer activities by preventing the degradation of IκBα and in turn blocking NF-κB activation. Moreover, Venkateswararao et al evaluated the inhibitory activity of a series of chalcone derivatives ( 59 , IC 50 : 1.17–3.43 µM) against NF-κB and their in vitro antiproliferative activity against various human cancer cell lines, and they found a good correlation between NF-κB inhibition through these derivatives and antiproliferative activity [ 158 ].…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…Similarly, 2-hydroxy-3’,5,5’-trimethoxychalcone (DK-139) ( 58 , Figure 13 ) inhibited the Toll-like receptor 4-mediated inflammatory response through suppression of the Akt//IKK/NF-κB signaling pathway in BV2 microglial cells [ 148 ]. In addition, isoliquiritigenin [ 149 , 150 , 151 ], flavokawain A and B [ 152 ], licochalcone A [ 153 ], cardamonin [ 154 , 155 , 156 ] and xanthohumol [ 157 ] all showed anti-inflammatory and anticancer activities by preventing the degradation of IκBα and in turn blocking NF-κB activation. Moreover, Venkateswararao et al evaluated the inhibitory activity of a series of chalcone derivatives ( 59 , IC 50 : 1.17–3.43 µM) against NF-κB and their in vitro antiproliferative activity against various human cancer cell lines, and they found a good correlation between NF-κB inhibition through these derivatives and antiproliferative activity [ 158 ].…”
Section: Representative Mechanisms Of Anticancer Action Of Chalconesmentioning
confidence: 99%
“…Isoliquiritigenin alleviated LPS-induced acute kidney injury by inhibition of the NF-κB pathway and TNF-alpha-induced release of HMGB ( Chi et al, 2017 ; Tang et al, 2018 ). Moreover, Isoliquiritigenin ameliorates renal Inflammation and fibrosis induced by unilateral ureteral obstruction ( Liao et al, 2020 ). It also, suppressed the Ang II-induced hypertensive renal injury via inhibiting inflammation cytokines, excessive deposition, and Nrf2 and NF-κB pathways ( Xiong et al, 2018 ).…”
Section: Reduction Of Covid-19-induced Oxidative Stress and Inflammatmentioning
confidence: 99%
“…Huber and others confirmed that inhibiting NF-κB signaling in Ras-transfected epithelial cells could prevent the occurrence of EMT, and activation of this pathway could promote the morphological transformation of cells to mesenchymal cells in the absence of TGF-β. In addition, the inhibition of NF-κB activity in mesenchymal cells can lead to a reversal of the EMT process, suggesting that NF-κB is necessary for the induction and maintenance of EMT [ 97 ]. NF-κB may be involved in the regulation of renal fibrosis, but the specific mechanism remains to be further studied (Fig.…”
Section: Signaling Pathway In Renal Fibrosismentioning
confidence: 99%